Implementing Enterprise Portfolio Management with Microsoft Project Server 2002 - Chefetz, Gary (Apress, 2012)
This systematic approach is the basis for the topical ordering in this book. Although some topics seem, at times, to be orphaned from their broader subjects, this is because they’re presented as you need them, when you encounter them during the natural setup and adoption process. Those of you using the book as a topical reference should understand the chronological flow of the book. I don’t organize many presentations of the user interface around a page or area itself. In learning about some areas, you’ll approach them several times to perform different system tasks. This way, your knowledge develops in context of actual system activity. Following a path guided by the interface wouldn’t provide as neat a context.